EFFECT OF DIFFERENT DRYING METHODS ON THE NUTRITIONAL AND SENSORY ATTRIBUTES OF ABELMOSCHUS ESCULENTUS (OKRA) - Agomuo, J. K.; Nasiru, B. U.; Ifeka, Calista (FUDMA JOURNAL OF SCIENCES, 2022)
This work was carried out to study the effect of different drying methods (shade, oven and sun drying) on the nutritional and sensory properties of Abelmoschus esculentus (okra vegetable). Results from this study showed that the carbohydrate content ranged from 11.64% in sample A to 54.20% in sample D, an increase due to the removal of moisture. The crude fat ranged from 0.52% to 3.40%. The ash content was markedly enhanced by drying too and it ranged from 1.30% in fresh sample to 8.91% in shade-dried sample, the fibre content ranged from 1.12% in fresh sample to 16.43 % in sun-dried sample. A slight decrease in mineral content was observed upon drying except sodium and magnesium which was found to be significantly higher in the fresh sample. There were increase in phosphorous and potassium upon drying. The vitamin content showed significant difference (p<0.05) in the level of vitamin C, it ranged from 3.68 mg/kg to 1.41mg/kg, the fresh sample ranked higher followed by shade, oven and sun-dried samples. The result for sensory quality attributes showed significance difference (p<0.05) in all the attributes of the okra soup made from the samples and shade dried sample gave the best result in terms of colour and taste which maybe low temperature processing that retained its sensory qualities. The result of this study suggests that drying improved the concentration of nutrients and could be useful in preserving Abelmoschus esculentus in a good way and ensure its availability all year round